Dietary Phytoestrogens: Neuroprotective Role in Parkinson's Disease - Goyal, Ahsas; Verma, Aanchal; Agrawal, Neetu (Current neurovascular research, 2021)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by progressive damage of mesencephalic dopaminergic neurons of the substantia nigra and the striatal projections. Recent studies suggest that estrogen and estrogen-like chemicals have beneficial effects on neurodegenerative diseases, particularly PD. Animal studies demonstrate that estrogen influences dopamine's synthesis, release, and metabolism. In vivo studies have also shown the significant beneficial effects of estrogen in shielding the brain from neurodegenerative processes like PD. Moreover, the expression and function of dopamine receptors can be modified by estrogen. Phytoestrogens are non-steroidal compounds derived from plants present in a large spectrum of foods, most specifically soy and in numerous dietary supplements. Phytoestrogens share structural and functional similarities with 17β-estradiol and can be used as an alternative treatment for PD because of estrogen's undesirable effects, such as the increased risk of breast and endometrial cancer, ischemic disorders, and irregular bleeding. Despite the beneficial effects of phytoestrogens, their impact on human health may depend on age, health status, and even the presence or absence of specific gut microflora. In addition to their antioxidant properties, soy products or phytoestrogens also exhibit neuroprotective activity in patients with PD via the interaction with estrogen receptors (ER) α and β, with a higher affinity for ERβ. Phytoestrogens offer a valuable model for fully exploring the biological effects of endocrine disruptors in general. However, observational studies and randomized controlled trials in humans have resulted in inconclusive findings within this domain. This review considered the evidence in animal models and human epidemiological data as to whether developmental exposure to various phytoestrogen classes adversely or beneficially impacts the neurobehavioral programming in PD.